ANALISIS DAYA DUKUNG LAHAN BERDASARKAN KEBUTUHAN DAN KETERSEDIAAN LAHAN PERTANIAN DI KABUPATEN GORONTALO UTARA - Syamsu ., Akuba; Bobby Jhon Vian Polii; Jailani ., Husain (Sam Ratulangi University, 2020)
The objectives of this study are: To study and analyze the availability of land in North Gorontalo District, Assessing and analyzing land requirements in North Gorontalo District, Analyzing and evaluating Carrying Capacity Ratio of agricultural land in North Gorontalo Regency. The research method is qualitative which is analyzed descriptively quantitative. The study was conducted covering 11 districts in North Gorontalo Regency. The data used in this study are primary data and secondary data, Data collection was obtained through direct observation at the research location and through literature studies from various trusted sources or related institutions namely the Central Statistics Agency of North Gorontalo Regency 2018, and the Department of Agriculture, Horticulture Plantation, North Gorontalo District 2018. The method for calculating the carrying capacity of land uses the method of analysis in accordance with Regulation of the Minister of Environment No. 17 of 2009. The results showed the availability of land (SL) of North Gorontalo Regency was 59,235,467 Ha, and the land requirement (DL) was 46,893,556 Ha. the value of land availability is greater than the need for land SL Ëƒ DL, carrying capacity for district level is categorized as surplus. Carrying capacity of agricultural land (CCR) in North Gorontalo District is obtained less than one or CCR <1 that is 0.36, the assumption is that the carrying capacity of agricultural land is deficit. Policy implications for the North Gorontalo District Government should emphasize sustainable agricultural development policies through intensification, extensification and revitalization programs, so that the carrying capacity of agricultural land can be increased in realizing self-reliance and sustainable regional food security.*eprm*